Sintered strength of ti-6Al-4V by metal injection molding (MIM) using palm stearin binder / N. H. Mohamad Nor...[et al.] - N. H., Mohamad Nor; M. H., Ismail; H., Husain; J. B., Saedon; M., Newishy (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Metal injection molding (MIM) is a metal working process used to compact Titanium, Ti-6Al-4V and the binder through injection moulding process. In this work, Titanium Ti-6Al-4V was mixed with palm stearin (PS) and polyethylene (PE) which act as a binder. Palm stearin (PS) is a potential binder system that can be used because it is inexpensive and highly available in Malaysia. Besides that, the application of MIM can reduce time and energy compared to the conventional process which high cost in production and difficulty of producing complex shape of materials. The green parts were then gone through of debinding process and sintering process. This project is to study the effect of the sintered Ti-Al-4V using palm stearin as a binder system. The properties of sintered specimen were investigated by physical properties such as its shrinkage and density. The average shrinkage of the sintered specimen was about 10.35% in length and 10.96% of width body of the specimen. Density of the sintered specimen was about 4.0343 g/cm3 and the tensile strength of the specimen was about 805.7 MPa.